2007
DOI: 10.1248/bpb.30.242
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cytokine-Mediated Nitric Oxide Synthase Expression in Rat Insulinoma Cells by Scoparone

Abstract: Autoimmune diabetes is characterized by a local inflammatory reaction in and around the pancreatic islets, followed by selective destruction of insulin-producing b-cells.1) Much evidence supports an effector role for cytokines in mediating b-cell destruction.2,3) Incubation of rat islets with interleukin1b (IL-1b) alone, or in combination with tumor necrosis factor (TNF)-a and interferon-g (IFN-g) results in the expression of the inducible form of nitric oxide synthase (iNOS), increased production of nitric ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…We have already reported on the protective effects of herbs and dietary supplements against cytokine-or cytotoxin-induced -cell damage via the suppression of iNOS expression (Park and Park, 2001;Kwon et al, 2003aKwon et al, , b, 2005Kwon et al, , 2006Kim et al, 2007). Many other groups have also attempted to save -cells from those insults by repressing either NF-B activation or NF-B-dependent iNOS expression (Scarim et al, 1998;Evans et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…We have already reported on the protective effects of herbs and dietary supplements against cytokine-or cytotoxin-induced -cell damage via the suppression of iNOS expression (Park and Park, 2001;Kwon et al, 2003aKwon et al, , b, 2005Kwon et al, , 2006Kim et al, 2007). Many other groups have also attempted to save -cells from those insults by repressing either NF-B activation or NF-B-dependent iNOS expression (Scarim et al, 1998;Evans et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In order to demonstrate predominantly the superiority of UPLC with quadruple time‐of‐flight mass spectrometry (QTof‐MS) in metabolite detection and identification, the rat metabolism of scoparone was investigated. Scoparone (6,7‐dimethoxycoumarin), a derivative of coumarin (1,2‐benzopyrone), is known to have potentially immunosuppressive, vascular relaxant, prevention of diabetes mellitus progression, and lipid lowering properties,12–16 and many studies have demonstrated that scoparone,17, 18 a representative compound in Yin Chen Hao Tang preparation, shows hepatoprotectivity, and thus could be used as a biomarker to evaluate the therapeutic effects of the formulae. The pharmacokinetics of scoparone are well understood,19, 20 and the metabolism of scoparone has been preliminarily investigated;21 however, those works only partly understood the metabolic performance; the analytical efficiency and conclusions were not thoroughly expected.…”
mentioning
confidence: 99%
“…We previously reported that herbs and dietary supplements had protective effects against cytokine-or cytotoxin-induced ß-cell damage that occurred through the suppression of iNOS expression (7,21,27,43,44). Numerous other studies have also attempted to demonstrate that ß cells could be protected from cytokine and cytotoxin-induced damage by repressing either NF-κB activation or NF-κB-dependent iNOS expression (45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%